2015
DOI: 10.1021/acs.est.5b00719
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Abiotic and Biotic Dechlorination Following Carboxymethyl Cellulose Stabilized Nanoscale Zero Valent Iron Injection

Abstract: A pilot scale injection of nanoscale zerovalent iron (nZVI) stabilized with carboxymethyl cellulose (CMC) was performed at an active field site contaminated with a range of chlorinated volatile organic compounds (cVOC). The cVOC concentrations and microbial populations were monitored at the site before and after nZVI injection. The remedial injection successfully reduced parent compound concentrations on site. A period of abiotic degradation was followed by a period of enhanced biotic degradation. Results sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 61 publications
5
55
0
Order By: Relevance
“…The correlation between ORP and H 2 is supported by field data. The three pilot projects that applied CMC‐nZVI showed very early and rapid rebound in ORP (i.e., less than five days after emplacement) (He et al., ; Kocur et al., ; Xiong et al., ), which is consistent with the fast corrosion rate of CMC‐nZVI observed in the bench studies. At the sites where BNP (prepared similarly as Fe BH ) was applied, ORP rebound occurred slightly later, around 5–6 days after injection, again consistent with the bench results showing Fe BH has a slightly longer half‐life than CMC‐nZVI (Elliott & Zhang, ).…”
Section: Field Characterization Of the Selectivity And Longevity Of Nzvisupporting
confidence: 60%
“…The correlation between ORP and H 2 is supported by field data. The three pilot projects that applied CMC‐nZVI showed very early and rapid rebound in ORP (i.e., less than five days after emplacement) (He et al., ; Kocur et al., ; Xiong et al., ), which is consistent with the fast corrosion rate of CMC‐nZVI observed in the bench studies. At the sites where BNP (prepared similarly as Fe BH ) was applied, ORP rebound occurred slightly later, around 5–6 days after injection, again consistent with the bench results showing Fe BH has a slightly longer half‐life than CMC‐nZVI (Elliott & Zhang, ).…”
Section: Field Characterization Of the Selectivity And Longevity Of Nzvisupporting
confidence: 60%
“…Field applications of NZVI did not show any prolonged negative effects on the microbial activity but even a stimulation of biological dechlorination (He et al, 2010;Kocur et al, 2015;Su et al, 2012;Wei et al, 2012) supporting the results of our study. Aging of NZVI as well as interaction with natural organic matter was shown to mitigate the toxicity of the NZVI (Baalousha, 2009;Bruton et al, 2015;Jang et al, 2014;Phenrat et al, 2009).…”
Section: Effect On Anaerobic-reductive Biological Dechlorinationsupporting
confidence: 89%
“…The formulation ingredients (coatings, suspending agents, stabilization materials) of NZVI preparations can also serve as a source of electron donors supporting biological dechlorination (He et al, 2010;Kirschling et al, 2010;Su et al, 2012;Wei et al, 2012). Despite toxic effects of NZVI on natural microflora and dechlorinating microorganisms (Barnes et al, 2010;Bruton et al, 2015;Kumar et al, 2014b;Velimirovic et al, 2015;Xiu et al, 2010aXiu et al, , 2010b, the combined use of abiotic dechlorination with NZVI and biological dechlorination can result in synergetic effects, positive for the remediation process (Bruton et al, 2015;He et al, 2010;Kocur et al, 2015;Su et al, 2012). High pH conditions developing during anaerobic ZVI corrosion as well as acidification due to fermentation of formulation ingredients being unfavourable for biological processes have to be taken into account during field applications (Bruton et al, 2015;Velimirovic et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Kuang, Zhou, Chen, Megharaj, and Naidu () found corroborating results supporting this theory, demonstrating that both nZVI and Ni/Fe composite NPs increased the biodegradation of phenol by Bacillus fusiformis at pH 6 and 8; nZVI was also demonstrated to increase biodegradation at low pH (pH 3). These laboratory findings are consistent with observations during applications of nZVI in the field, where biological reductive dechlorination continues or is stimulated (e.g., He, Zhao, & Paul, ; Kocur et al., ). Indeed, Lacinová, Černíková, Hrabal, and Černík () showed that in field tests sequentially combining nZVI and in situ biostimulation achieved greater reduction in chlorinated solvents in a contaminated aquifer (76 percent compared to 48 percent for nZVI alone).…”
Section: Risk‐benefit Appraisal For Nanorem Technologiessupporting
confidence: 87%